The Implications of User-Generated Content (UGC) for Digital Marketing Strategies in Indonesia: A Systematic Literature Review of Research Trends and Key Insights Over the Past Decade (2015–2025) - Chintia Romadayanti; Vivin Wulandari (International Journal of Advanced Research in Social Studies, 2026)
This study aims to evaluate the development, contribution, and strategic direction of User-Generated Content (UGC) in digital marketing practices in Indonesia through a systematic literature review approach based on the PRISMA method. A total of 27 scholarly articles published between January 2015 and May 2025 were thematically analyzed to identify publication trends, methodological approaches, and the impact of UGC on consumer behavior and brand strategies. The analysis results show that UGC has become a strategic element in building brand authenticity, increasing customer engagement, and influencing purchase intentions and consumer loyalty. Digital platforms such as TikTok and Instagram play a significant role in amplifying the effects of UGC, especially among younger generations and online communities. However, integrating UGC into long-term strategies still faces challenges such as content quality, impact measurement, and limitations in population segmentation. This study recommends strengthening community-based approaches, adopting UGC performance analytics tools, and exploring further research in more diverse sectors and platforms. These findings are expected to enrich academic literature and provide practical guidance for brand managers in managing participatory and sustainable digital content.